The Ancestral Domain Claim of the Impahanog - Amusig Tribal Council Organization - B. Rodil, Rudy; Sevidal- Castro, Luz C.; Tangian , Maria Cecilia (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This is a documentation of the ancestral domain claim of the Higaunons of Impahanong and Amusig in Malitbog, Bukidnon. They are part of the larger group of Higaunons who belong to the walu ha talugan or the eight territories of the tribe that stretches from Agusan del Norte, westward across Bukidnon and Misamis Oriental up to Rogongon, Iligan City in Lanao del Norte - all associated with big rivers that spill into the sea. The eight are Odiongan (Gingoog), Agusan, Kabulig (Claveria), Tagoloan, Lanao, Cagayan. Pulangi (Bukidnon) and Balatukan (Balingasag) As far back as this indigenous community can recall, their occupancy of their ancestral domain goes back to at least eight generations, or using the universally accepted 30 years per generation as a gauge, the equivalent of 240 years This is far in excess of what the government requires to justify the issuance of a certificate of ancestral domain claim. Re-enforcing their claim are communn lore on the names of places and sites. as well as their tradition and custom on land acquisition and land use